Elements of Community Capacity Building (CCB)for CBET development - Mohd Noh, A. N; Razzaq, A. R. A.; Mustafa, M. Z.; Nordin, M. N.; Ibrahim, B. (2020)
Ecotourism is an alternative form of tourism and is usually confused with natural and cultural tourism.CBET is fast becoming a popular biodiversity conservation tool that develops and benefits the local community. Based on the context of conservation theory and practice, Community-Based Ecotourism (CBET) is a form of community-based natural resource management. However, a sustainable CBET development through Community Capacity Building (CCB)programs is not something that it easily achievable. Local community’s capacity varies from one culture to another. It takes a high level of community participation, in order for it to come to a level where the community members themselves are motivated to participate and contribute to the development of the program. This fully qualitative research involved 15 respondents from the community of Kg. Selai, Bekok in Johor, Malaysia. The result show there are five factors that sustained the ecotourism development based for Orang Asli Community in Kg. Selai, namely, existing CBET development, past CBET development, local community participation in planning stage of tourism, local participation in implementation stage of tourism and participation in nature conservation.